Characterization of non-dialyzable constituents from cranberry juice that inhibit adhesion, co-aggregation and biofilm formation by oral bacteria. Issue 5 (4th May 2017) - Neto, C. C.; Penndorf, K. A.; Feldman, M.; Meron-Sudai, S.; Zakay-Rones, Z.; Steinberg, D.; Fridman, M.; Kashman, Y.; Ginsburg, I.; Ofek, I.; Weiss, E. I.
Abstract : A mixture of compounds identified in non-dialyzable fraction from cranberry juice inhibits adhesion, coaggregation and biofilm formation by oral bacteria. Abstract : An extract prepared from cranberry juice by dialysis known as nondialyzable material (NDM) has been shown previously to possess anti-adhesion activity toward microbial species including oral bacteria, uropathogenic Escherichia coli and Helicobacter pylori . Bioassay-guided fractionation of cranberry NDM was therefore undertaken to identify the anti-adhesive constituents. An aqueous acetone-soluble fraction (NDMac) obtained from Sephadex LH-20 inhibited adhesion-linked activities by oral bacteria, including co-aggregation of oral bacteria Fusobacterium nucleatum with Streptococcus sanguinis or Porphyromonas gingivalis, and biofilm formation by Streptococcus mutans . Analysis of NDMac and subsequent subfractions by MALDI-TOF MS and 1 H NMR revealed the presence of A-type proanthocyanidin oligomers (PACs) of 3–6 degrees of polymerization composed of ( epi )catechin units, with some ( epi )gallocatechin and anthocyanin units also present, as well as quercetin derivatives. Subfractions containing putative xyloglucans in addition to the mixed polyphenols also inhibit biofilm formation by S. mutans (MIC = 125–250 μg mL −1 ). These studies suggest that the anti-adhesion activities of cranberry NDM on oral bacteria may arise from a combination of mixed polyphenol and non-polyphenol constituents.